ENAM METODE MENGHAFAL AL-QURAN MAHASISWA DI PERGURUAN TINGGI AL-QURAN INDONESIA - Oktavia, Gifa; Hasnah, Hasnah; Febriani, Afifah; Sabrina, Vinni; Rahman, Ikhwan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Memorizing the Quran is a very noble activity, it is not just a label of glory that will be obtained by those who memorize the Quran, but also provides intercession for their parents. To be able to memorize 30 juz of the Quran is not an easy matter, because it requires seriousness, motivation and appropriate methods in memorizing the Quran. This research aims to explore the methods used by students in memorizing the Quran at Indonesian Quran Colleges. This research uses a qualitative method with a case study type. Data sources were taken from twenty informants through direct interviews using a set of interview protocols. The informants involved were selected using a purposive sampling technique, from three intake year classes, namely 2019, 2020 and 2021. All interview data obtained was analyzed theoretically using the Milles & Hubberman Interactive Analysis Model technique. Research findings found six dominant methods used by Indonesian Quran College students in memorizing the Quran. The six methods are i) bi al-nadzar method, ii) sima'i method, iii) thariqah tasalsuli method, iv) thariqah jam'i method, v) thariqah muqassam method, vi) wahdah method. This research has revealed the dominant methods used in memorizing the Quran. Apart from that, the results of this research can be used as a reference for anyone who wants to become a memorizer of the Quran.